Efektifitas Kelambu Berinsektisida Long Lasting Insecticidal Nets (LLINS) terhadap Anopheles maculatus: Effectiveness of Long Lasting Insecticidal Nets (LLINS) against Anopheles maculatus - Febriyanto; I Gede WD; Irpan Pahlepi, Rahman; Santoso, Santoso; Mahdalena, Vivin; Taviv, Yulian; Komaria, Rahayu Hasti; Sutanto, Himawan; Riandi, Muhammad Umar (Aspirator, 2024)
Malaria is a vector-borne disease problem in several parts of Indonesia, including the Rejang Lebong Regency, Bengkulu Province. One way to break the chain of malaria transmission is by using insecticide-treated mosquito nets. The effectiveness of using insecticide-treated mosquito nets in the community needs to be studied. This study was conducted to evaluate the effectiveness of insecticide-treated mosquito nets against Anopheles maculatus based on the duration of use by the community. A fully randomized design study was used to compare the effectiveness of mosquito nets used for six months, six months to two years, and more than two years from 3 different sub-districts. The method used was the WHO bioassay cone test with an untreated polyester mosquito net as a control. Female Anopheles maculatus was tested in a cone bioassay and transferred to paper cups to observe for knockdown or death after 10, 30, and 60 minutes to 24 hours. The results showed that the mosquito nets used for <1 year resulted in 92% knockdown and 80% death. Meanwhile, the use of mosquito nets for 1-2 and >2 years resulted in 92.6% and 75.2% knockdown mosquitoes and 78% and 67.8% dead mosquitos. We concluded that insecticide-treated mosquito nets used for less than one year were still effective for use in controlling malaria.Routine monitoring and evaluation should be carried out to assess the effectiveness of the mosquito nets used.